Parabatai Bond’s Attachment Styles In Cassandra Clare’s Lady Midnight - Luvila Al Fitra; Ariya Jati (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
Lady Midnight is an urban fantasy novel which centralizes around the special bond of the main characters, Emma Carstairs and Julian Blackthorn called parabatai. Parabatai designates a distinctive type of characterization, and the type ignites the writer’s interest to study further. This study intends to describe the characteristics of urban fantasy and attachment styles of the parabatai bond present in the novel. This study would be carried out as a library study. The analysis would come in two parts: the characteristics of urban fantasy and the attachment styles between Emma Carstairs and Julian Blackthorn. This study would be beneficial for those who wish to understand more about urban fantasy and attachment styles in a novel. As one of the most well-known works of Cassandra Clare, this novel discloses a broad description of urban fantasy and attachment styles.Keywords: urban fantasy; attachment styles; parabatai; shadowhunter; community law